The health belief model: How public health can address the misinformation crisis beyond COVID-19 - Shandell Houlden; Jaigris Hodson; George Veletsianos; Darren Reid; Chris Thompson-Wagner (Elsevier, 2021)
Objectives: This paper proposes an intervention into health misinformation that relies upon the health belief model as a means to bridge the risks associated with health misinformation and the impact on individual health, beyond the current recommendations for fact checking and information literacy. Study design: This is a short theoretical paper. Methods: N/A. Results: N/A. Conclusions: Misinformation researchers and public health practitioners and communicators can benefit using the infrastructures afforded by public health offices to mobilize the health belief model as a site for misinformation education.